Pengembangan Model Manajemen Pendidikan Kepramukaan Berbasis Multikultural - Sofwan Sofwan (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2020)
Scouting education based on multiculturalism is currently the main concern of junior high schools in Indonesia. The low multiculturalism as a form of decline in the nation's character is due to the weakness of multicultural-based education in the education unit. Scout management models are not yet available as an effective instrument for shaping multicultural attitudes. The problem of this research is directed at the development of multicultural-based scouting management education models in junior high schools. This study aims to: 1) describe multicultural-based scouting education in junior high schools in Demak Regency, 2) develop a multicultural-based scouting management management model design in junior high schools and 3) test the feasibility of developing multicultural-based scouting management education models for students. The approach used is a qualitative approach with research and development (R&D) methods. Research locus in 5 (five) junior high schools in Demak Regency. Data is collected through in-depth interviews, observation, documentation, validation of experts and practitioners. The validity of the data uses four criteria, namely the degree of trust (credibility), transferability, dependability and confirmation. Data analysis uses interactive analysis through data collection, data reduction, data presentation and conclusions. Research results: 1) Scouting management education in junior high schools varies, has not been standardized and normative according to the characteristics of the education unit. 2) the development of scouting management management models including planning, organizing, implementing and controlling, involving the principal, stakeholders, frontline, scoutmaster, students through extracurricular activities. 3) the feasibility of developing a Scouting education management model influenced by (a) the scouting education management standard (b) the availability of developing an educational management model (c) the planned, structured, measurable and sustainable scouting education process (d) the availability of individual readiness and stakeholder involvement, (e) the existence of guiding scout coaches and (f) giving appreciation to students. The conclusions of this study are a) the management of scouting education in junior high schools in Demak Regency varies and has not been standardized b) the development of scouting management management models including planning, organizing, implementing and controlling and c) the feasibility of scouting education management is influenced by six success factors. Suggestions of this research are a) the Ministry of Education and Culture, to apply the scouting education management model b) kwarnas to study the development of this model as a strategy for the success of character education and c) kwarda, kwarcab., And kwarran. in order to review the development of the model.